Post Dural Puncture Headache after Cesarean Section, a Teaching Hospital Experience - Farhad Etezadi; Fardin Yousefshahi; Mohammadreza Khajavi; Fateme Tanha; Alireza Dahmarde; Atabak Najafi (Tehran University of Medical Sciences, 2012)
Objective: This prospective study examined the frequency of Post-Dural Puncture Headache (PDPH) in 361 parturient women undergoing spinal anesthesia for cesarean section in a teaching hospital of Tehran University of Medical Sciences. Materials and methods: Spinal anesthesia was performed using 25 gauge Quincke needles in all women. Patients were followed up to determine incidence of PDPH and then tried to compare those with or without PDPH using statistical methods to determine risk factors of PDPH. Results: The overall incidence of PDPH was 10.8 percent in this study. In terms of probable risk factors which were compared between the two groups of patients, no statistically significant differences were found. Conclusion: The incidence of PDPH in our study was higher than studies which used pencil - tipped needles and we determined that the occurrence of PDPH is not associated to some factors like the previous history of nonspecific headache, Body Mass Index, age, type of local anesthetic, previous history of PDPH, experience of operator, history of habitual tea and coffee drinking.